Mechanisms of redox interactions of bilirubin with copper and the effects of penicillamine. (25th December 2017) - Božić, Bojana; Korać, Jelena; Stanković, Dalibor M.; Stanić, Marina; Popović-Bijelić, Ana; Bogdanović Pristov, Jelena; Spasojević, Ivan; Bajčetić, Milica
Abstract: Toxic effects of unconjugated bilirubin (BR) in neonatal hyperbilirubinemia have been related to redox and/or coordinate interactions with Cu 2+ . However, the development and mechanisms of such interactions at physiological pH have not been resolved. This study shows that BR reduces Cu 2+ to Cu 1+ in 1:1 stoichiometry. Apparently, BR undergoes degradation, i.e. BR and Cu 2+ do not form stable complexes. The binding of Cu 2+ to inorganic phosphates, liposomal phosphate groups, or to chelating drug penicillamine, impedes redox interactions with BR. Cu 1+ undergoes spontaneous oxidation by O2 resulting in hydrogen peroxide accumulation and hydroxyl radical production. In relation to this, copper and BR induced synergistic oxidative/damaging effects on erythrocytes membrane, which were alleviated by penicillamine. The production of reactive oxygen species by BR and copper represents a plausible cause of BR toxic effects and cell damage in hyperbilirubinemia. Further examination of therapeutic potentials of copper chelators in the treatment of severe neonatal hyperbilirubinemia is needed. Graphical abstract: Highlights: Bilirubin reduces Cu 2+ in 1:1 stoichiometry. Cu 1+ undergoes spontaneous oxidation resulting in reactive oxygen species production. Copper and bilirubin induce oxidative damage in cell membranes. Redox interactions of Cu 2+ and bilirubin are hampered by penicillamine and phosphates.